The Concept of Retrofitting Suburban in Commercial Corridor - Sonia Nadia Ruth Madelene Sitompul; Dwi Lindarto Hadinugroho (Talenta Publisher, 2022)
Pasar Ikan Lama, located on the Commercial Road, is a well-known commercial area in Medan. The location is close to the city center so that local and foreign tourists easily find it. The place dominates by cloth sales such as kebaya wholesaler center, headscarves, Mukenah, prayer mats, carpets, batik, traditional clothing, and their items are originating from Makah such as dates and zam-zam water. The phenomenon that is now occurring in the Pasar Ikan Lama is an untidy arrangement. Another phenomenon is the strategic position that is adjacent to the historical area. Even so, the Pasar Ikan Lama is still visited. Visitors come not only from Medan but from various regions to foreign countries. The Pasar Ikan Lama can use as a destination or icon for the City of Medan. Therefore, it is necessary to revitalize it to increase vitality in the area of ​​the Pasar Ikan Lama. Revitalization model for the Medan commercial corridor with the concept of suburban retrofitting carried out using the theory of Suburban Retrofitting as a basis, accordingly the idea of Hamid Shirvani as a determinant of needs from a commercial corridor, Lynch theory is beneficial as a determinant of something interesting, potentially to be developed or abolished. The results of the study obtained from this study are the revitalization model of the Medan City commercial corridor with the concept of suburban retrofitting